Carboxylic Acid Key Role in Life Sciences - Ileana Badea, Georgiana; Lucian Radu, Gabriel (IntechOpen, 2018)
This book is an attempt to bring together current knowledge on the role and importance of organic acids in life processes. There are lots of compounds based on the chemical nature of this functional group, which makes this class of molecules to be present in our lives starting with the human body (Krebs cycle - the core of cellular metabolism) to the products we currently use (food, medicines and cosmetics). No overall consensus is sought in this book, and the following chapters are authored by dedicated researchers presenting a diversity of applications and hypotheses concerning organic acids. The five chapters in this book include general information on carboxylic acids and their applications in life sciences (use in organic synthesis, nanotechnology, plant physiology, plant nutrition and soil chemistry).